1999
DOI: 10.1074/jbc.274.42.30190
|View full text |Cite
|
Sign up to set email alerts
|

ATP and the Core “α-Crystallin” Domain of the Small Heat-shock Protein αB-crystallin

Abstract: Electrospray ionization mass spectrometry (ESI-LC/ MS) of tryptic digests of human ␣B-crystallin in the presence and absence of ATP identified four residues located within the core "␣-crystallin" domain, Lys 82 , Lys 103 , Arg 116 , and Arg 123 , that were shielded from the action of trypsin in the presence of ATP. In control experiments, chymotrypsin was used in place of trypsin. The chymotryptic fragments of human ␣B-crystallin produced in the presence and absence of ATP were analyzed using liquid chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 71 publications
6
46
1
Order By: Relevance
“…Nonhydrolyzable ATP analogs had no stimulatory effect. Tryptophan fluorescence studies and mass spectrometry of tryptic digests of the chaperone demonstrated ATP-dependent structural modifications in the ␣-crystallin domain, which might influence its functionality (216,217). ATP-enhanced chaperone activity of ␣B-crystallin was independently confirmed in experiments with the bovine protein (297).…”
Section: Function Of ␣-Heat Shock Proteins In Protein Quality Controlmentioning
confidence: 70%
“…Nonhydrolyzable ATP analogs had no stimulatory effect. Tryptophan fluorescence studies and mass spectrometry of tryptic digests of the chaperone demonstrated ATP-dependent structural modifications in the ␣-crystallin domain, which might influence its functionality (216,217). ATP-enhanced chaperone activity of ␣B-crystallin was independently confirmed in experiments with the bovine protein (297).…”
Section: Function Of ␣-Heat Shock Proteins In Protein Quality Controlmentioning
confidence: 70%
“…Limited tryptic digestion studies of ␣-crystallin reported by us (38) as well as by others (31) showed that cleavage sites located at the C-and N-terminal regions are relatively easily accessible by trypsin, but those on the ␣-crystallin domain are less accessible. We have checked whether the addition of ATP leads to any differences in the accessibility of these sites of ␣A-crystallin by trypsin.…”
Section: Enhanced Structural Stability Of ␣-Crystallin In the Presencmentioning
confidence: 99%
“…In the case of bacteria, sHSPs may be absent in some species, e.g., Mycoplasma genitalium, while in other species only a small number of sHSP-encoding genes are present, such as in the case of Escherichia coli, which specifies just two types of sHSPs (13). In contrast, rhizobia possess a large set of genes specifying sHSPs (12).…”
mentioning
confidence: 98%